A Comprehensive Review of Engineering, Procurement, and Construction in Nigeria - Imoni, Samson; Akande, Ebenezer Ogirima; Jiya, Victoria Hassana; Onuzulike, Collins; Tiza, Michael Toryila (Journal of Management Studies and Development, 2023)
This study focuses on the challenges and prospects of engineering procurement in Nigeria. The research examines the existing literature on engineering procurement practices, identifies gaps in knowledge, and explores potential areas for improvement. Through a comprehensive review, key findings emerge, highlighting limited research specific to engineering procurement in Nigeria and a lack of empirical studies on project performance and outcomes. Moreover, the literature review reveals a need for more research on engineering procurement projects' socio-economic and environmental impacts. The implications of these findings underscore the need for targeted research, enhanced data collection, and monitoring mechanisms to evaluate project performance accurately. Additionally, the study emphasises the importance of considering the broader socio-economic and environmental implications for sustainable development. Overall, this study serves as a foundation for advancing the understanding of engineering procurement in Nigeria and offers insights for policy-makers, researchers, and practitioners in the field.